Prediction of wave resistance by a Reynolds-averaged Navier-Stokes equation-based computational fluid dynamics approach - Kinaci, Omer K.; Sukas, Omer F.; Bal, Sakir (SAGE PUBLICATIONS LTD, 2016)
The prediction of wave resistance in naval architecture is an important aspect especially at high Froude numbers where a great percentage of total resistance of ships and submerged bodies is caused by waves. In addition, during hull form optimization, wave resistance characteristics of a ship must closely be observed. There are potential, viscous and experimental methods to determine the wave resistance of a ship. Reynolds-averaged Navier-Stokes equation-based methods usually follow the experimental method that determines the form factor first. However, it is proven in recent studies that the form factor changes with the Reynolds number. As the Reynolds number increases, this change in the form factor is being neglected. In this study, a Reynolds-averaged Navier-Stokes equation-based prediction of wave resistance is presented that overcomes this flaw. The methodology is validated with the benchmark problems of submerged and surface-piercing bodies to determine the effectiveness of the proposed method. The method is also validated by experiments carried out at the Ata Nutku Ship Model Testing Laboratory of Istanbul Technical University for a totally submerged ellipsoid and the benchmark KRISO Containership. Results reveal the robustness of the present methodology.
Keywords: Wave resistance; viscous resistance; Reynolds-averaged Navier-Stokes equation; KRISO Containership; form factor; SURFACE-PIERCING BODIES; BOUNDARY-LAYER; SHIP; WATER; FLOW; SIMULATION; VOLUME; WAKE; BEM; Engineering